ARTS OF PENCAK SILAT STYLE FOR EDUCATION SPIRITUAL AND PHYSICAL - Suryo Ediyono (Proceeding IICACS, 2019)
The martial art of pencak silat isa combating method that teaches both spiritual and physicaleducationphilosophically helps the enthusiasts to livethe noble moral valuesin their society. The material object of this study is pencak silat andthe formalobjectis thephilosophy of artsoraesthetics. This studyaims to examine(1) norms or manners of pencak silat,(2) pencak silat style, (3) categories of pencak silatandpencak silatequipments. This research employs factual-historical method by means of description, analysisandsynthesis. Theresults are(1) norms of pencak silat are conceptually found in the attitude of performance, steps (gerak langkah), attack (serangan), and defense (belaan),(2) martial arts style (aliran gaya) consists of the mental-spiritual aspects, martial arts, arts, and, sport,(3) arts in martial artsare subdivided intowiraga, wirama, andwirasaandthe martialartsequipments includespecific use of costumes, weapons and traditional music acompaniment.Keywords: arts; philosophy; pencak silat; styles; equipments